Perkembangan Emosional Anak Usia Dini dalam Transisi ke Sekolah: Tinjuan Literatur tentang School Phobia - Dayati Erni Cahyaningrum; Arri Handayani; Dini Rahmawati (Departement of Mathematics Education, 2024)
Early childhood children who enter the preschool period certainly experience a transition with changes that affect emotional development, in this case it can result in school phobia, which means refusal to go to school. In this research, researchers using literature studies found ten articles via Google Scholar with the keywords school refusal, school phobia, school phobia, school phobia preschool, and preschool transition with the aim of gaining knowledge regarding these matters. The research results show that school phobia in the transition period which affects emotional development can be overcome by collaborating with teachers, parents and the child through identifying the causal factors.